The Agricultural Land Market in Ukraine: Current Conjuncture and Problems of Formation - Т. LUNOVA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
The agricultural land market was launched in Ukraine on July 1, 2021. Before its opening in Ukraine, experts had attempted to outline various scenarios of its operation, but most part of the predictions proved to be far from reality. The inadequacy and unsoundness of these predictions raise the importance of studies devoted to the current conjecture of the agricultural land market in Ukraine.    The article contains results of a study of the processes involved in the formation of the agricultural land market in Ukraine and its current conjuncture. A review of the legal acts of Ukraine that streamlined the evolution of relations on this market was made: the Decree of the President of Ukraine “Urgent measures to accelerate reforms in the agrarian sector of the economy” (1999), the Land Code of Ukraine (2001), the Decree of the President of Ukraine “Supplementary measures on social protection of rural residents who are owners of land plots and land parts (shares)” (2002), the Law of Ukraine “Amendments to some legislative acts of Ukraine on terms of the turnover of agricultural lands” (2020). A comparison of the cost of land lease in Ukraine and EU countries in 2019, and the actual weighted average price of 1 hectare of agricultural land in Ukraine and some other countries was made. Domestic sources of information on the land market operation in Ukraine are given.     It is concluded that the land market in Ukraine is in the passive state now, with both demand and supply being slack. The factors behind the low demand and supply on the domestic land market were identified: the demand is constrained by a limited range of buyers and lack of uncostly mortgage loans for purchase of land; the supply is constrained by the low market price of 1 hectare of land, inability of the majority of residents to sell their shares in case of the valid leasing contract, bad legal and financial literacy of rural inhabitants. The efficiency of land leasing in Ukraine remains to be low due to irrational use of soils by land tenants. The need for government regulation of this market is shown.